Protein requirements of early-weaned Dorper crossbred female lambs - Tao MA; Kai-dong DENG; Yan TU; Nai-feng ZHANG; Bing-wen SI; Gui-shan XU; Qi-yu DIAO (Journal of Integrative Agriculture)
The net protein (NP) and metabolizable protein (MP) requirements of Dorper crossbred female lambs from 20 to 35 kg body weight (BW) were assessed in a comparative slaughter trial. Thirty-five Dorper×thin-tailed Han crossbred lambs weaned at approximately 50 d of age ((19.1±2.37) kg of BW) were used. Seven randomly selected lambs were slaughtered at the beginning of the trial as baseline group (BL). An intermediate group of seven randomly selected lambs fed ad libitum (AL) intake was slaughtered when the lambs reached an average BW of 28.6 kg. The remaining 21 lambs were allotted randomly to three levels of dry matter intake: AL or restricted to 70 or 40% of the AL intake. All lambs were slaughtered when the sheep fed AL intake reached 35 kg of BW. Total body N and N retention were determined. The results showed that the maintenance requirements for NP and MP were 1.75 and 3.37 g kg−1 metabolic shrunk body weight (SBW0.75), respectively. The partial efficiency of protein use for maintenance was 0.52. The NP requirements for growth ranged from 10.9 to 42.4 g d−1 for the lambs gaining 100 to 350 g d−1 from 20 to 35 kg BW. The partial efficiency of MP for growth was 0.52. In conclusion, the NP and MP requirements for the maintenance and growth of Dorper crossbred female lambs were lower than those reported by AFRC (1993) and NRC (2007) recommendations.